Facial Conformation Modeling by Anthropometric Measurements - Vila Nova, Arnaldo Barreto; Vidal, Creto Augusto; Cavalcante-Neto, Joaquim B.; Carneiro, Lílian de Oliveira (Anais do Simpósio de Realidade Virtual e Aumentada (SVR); 2024: Anais do XXVI Simpósio de Realidade Virtual e Aumentada, 2024)
This paper presents a method for modeling facial conformation using anthropometric measurements. The technique is designed to ensure seamless surface continuity and scalability for incorporating new measurements. The method allows for the manipulation of both global and local facial characteristics, provided the anthropometric points are present. It organizes the anthropometric measurements into a three-level hierarchy with global, regional, and local facial features. Then, deformations are applied to a base facial mesh representation to adjust it to the landmarks and achieve the desired facial measures. In this work, the results focus on modifications of the mouth region of a base model, showcasing the method’s ability to alter features such as mouth width and lip thickness. The paper discusses the current limitations of the proposed technique and points to some improvements in future works.